2007
DOI: 10.1002/chin.200722132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amide Derivatives of Quinolone and Their Antimicrobial Studies.

Abstract: Synthesis of Amide Derivatives of Quinolone and Their Antimicrobial Studies. -A large variety of quinolinyl amides [cf. (IX), (XI); 70 examples] is synthesized. Several derivatives, e.g. (IXb)-(IXe), (XIa), exhibit significant antibacterial activity. -(PATEL, N. B.; PATEL, A. L.; CHAUHAN, H. I.; Indian J. Chem., Sect. B: Org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The preparation of γ-PGA-based hydrogels, the bonding of carboxyl group to nanoparticles, and development of γ-PGA and gelatin-based ionic hydrogels are gaining popularity ( Garcia et al, 2014 ; Gao C. et al, 2016 ; Chen et al, 2023 ; Yu et al, 2023 ). γ-PGA-derived biocompatible antimicrobial hydrogels (TCS (Triclosan), CHX (Chlorhexidine), and PHMB (Polyhexamethylene biguanide)) have been prepared using electrospun nanofibers and bulk, which displayed promising antimicrobial efficacy against gram-positive staphylococcus aureus and gram-negative E. coli ( Patel et al, 2007 ; Vedadghavami et al, 2017 ; Kasbiyan et al, 2022 ). The antimicrobial activity of chitosan-γ-PGA polyelectrolyte complex hydrogels and γ-PGA-coated magnetite particles have been reported against S. aureus and E. coli ( Tsao et al, 2010 ; Inbaraj et al, 2011 ).…”
Section: Applications Of γ-Pgamentioning
confidence: 99%
“…The preparation of γ-PGA-based hydrogels, the bonding of carboxyl group to nanoparticles, and development of γ-PGA and gelatin-based ionic hydrogels are gaining popularity ( Garcia et al, 2014 ; Gao C. et al, 2016 ; Chen et al, 2023 ; Yu et al, 2023 ). γ-PGA-derived biocompatible antimicrobial hydrogels (TCS (Triclosan), CHX (Chlorhexidine), and PHMB (Polyhexamethylene biguanide)) have been prepared using electrospun nanofibers and bulk, which displayed promising antimicrobial efficacy against gram-positive staphylococcus aureus and gram-negative E. coli ( Patel et al, 2007 ; Vedadghavami et al, 2017 ; Kasbiyan et al, 2022 ). The antimicrobial activity of chitosan-γ-PGA polyelectrolyte complex hydrogels and γ-PGA-coated magnetite particles have been reported against S. aureus and E. coli ( Tsao et al, 2010 ; Inbaraj et al, 2011 ).…”
Section: Applications Of γ-Pgamentioning
confidence: 99%
“…We observed from the literature survey that the fluoroquinolones with hydrolyzable group, viz. amide and ester (Patel and Bhagat, 2006;Patel and Modi, 2006;Patel et al, 2007;Sharma and Jain, 2008), were synthesized and some of the compounds were found potent. Hence, we decided to synthesize thiazolidinones and Schiff bases incorporated fluoroquinolones through the hydrolyzable amide linkage to observe the variation in antimicrobial activity (Scheme 1).…”
mentioning
confidence: 99%